Pharmacokinetics, pharmacodynamics, safety and tolerability of dabigatran etexilate oral liquid formulation in infants with venous thromboembolism - Halton, Jacqueline; Brückmann, Martina (Thrombosis and haemostasis, 2017)
Venous thromboembolism (VTE) is more frequent in infants than in older children. Treatment guidelines in children are adapted from adult VTE data, but do not currently include direct oral anticoagulant use. Dabigatran etexilate (DE) use in the paediatric population with VTE therefore requires verification. We investigated the pharmacokinetic/pharmacodynamic (PK/PD) relationship, safety and tolerability of DE oral liquid formulation (OLF) in infants with VTE (aged < 12 months) who had completed standard anticoagulant treatment in an open-label, phase IIa study. Patients received a single-dose of DE OLF (based on an age- and weight-adjusted nomogram) yielding an exposure comparable to 150 mg in adults. The PK end point was plasma concentration of total dabigatran; PD end points included activated partial thromboplastin time (aPTT), ecarin clotting time (ECT) and diluted thrombin time (dTT). Safety end points included incidence of all bleeding and other adverse events (AEs). Ten patients were screened; eight entered the study (age range, 41-169 days). The geometric mean (gMean) total dabigatran plasma concentrations 2 hours post-dose (around peak concentrations) were 120 ng/mL with a geometric coefficient of variation (gCV) of 62.1%. The gMean at 12 hours post-dosing was 60.4 ng/mL (gCV 30%). PK/PD relationship was linear for ECT and dTT (R 2 = 0.858 and 0.920, respectively), while total dabigatran concentration and aPTT showed a non-linear correlation. There were no deaths, treatment discontinuations or treatment-related AEs. In conclusion, DE was well tolerated without any treatment-related AEs in infants. The observed PK/PD relationships were comparable with the established profile in older patients with VTE.
Publikationsdatum: 30. November 2017 (online)
Gesehen am 21.06.2018